2004
DOI: 10.1002/pssa.200405164
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen plasma pre-treatments for high quality homoepitaxial CVD diamond deposition

Abstract: In this study, homoepitaxial diamond films were grown on HPHT Ib synthetic diamonds by microwave plasma assisted CVD (MWPACVD) using a two step process. Etching of the diamond substrates prior to growth was performed in oxygen-hydrogen or oxygen-argon-hydrogen plasmas for different etching times. After this step, homoepitaxial growth was performed for 20 hours. High quality monocrystalline diamond films have been synthesized as confirmed by Raman and photoluminescence spectra and growth rates close to 2.5 µm/h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(52 citation statements)
references
References 2 publications
0
51
0
1
Order By: Relevance
“…Meanwhile, it has been showed in the several previous studies that the polishing defects of the diamond substrate propagate into homoepitaxial layers, leading to plastic deformations and trapping of carriers into deep defects [8][9][10][11][12][13]. In a previous study [14], it has been showed that a plasma etching treatment applied to the substrate before film growth can remove defects of the Ib (100) HPHT diamond substrates and induces an increase of the homoepitaxial diamond film quality.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, it has been showed in the several previous studies that the polishing defects of the diamond substrate propagate into homoepitaxial layers, leading to plastic deformations and trapping of carriers into deep defects [8][9][10][11][12][13]. In a previous study [14], it has been showed that a plasma etching treatment applied to the substrate before film growth can remove defects of the Ib (100) HPHT diamond substrates and induces an increase of the homoepitaxial diamond film quality.…”
Section: Introductionmentioning
confidence: 99%
“…It is not expected that the addition of Ar is crucial, however it has been previously reported to be effective in increasing the etching rate under certain conditions [185]. The aim of this step was to remove any non-diamond carbon residue that may remain on the surface of the sample, which could act as unwanted nucleation sites.…”
Section: Resultsmentioning
confidence: 99%
“…New species formed in the plasma (i.e., O -and OH -) etch away impurities (hydrogen, and sp 2 carbon) and defects on growth surface more efficiently than atomic hydrogen, and therefore improve the diamond quality. Furthermore, oxygen addition can hinder diamond cracks, thereby promoting growth of thicker single crystal layers [29,30].…”
Section: Optical Characterization Of Cvd Single-crystal Diamondmentioning
confidence: 99%